Exploring the views of general practitioners (GPs), pharmacists and the public regarding issues related to dispensing separation: a pilot study - Salim, Mohamad Hafis (2016)
Issues of dispensing separation (DS) have been in the news recently. Malaysian Pharmaceutical Society (MPS) have been persistently trying to discuss for the implementation of this separation policy. Currently, in the private sector in Malaysia, especially the community settings, the dispensing tasks are performed by general practitioners' (GPs) assistants limiting community pharmacists' job scope. The GPs are not in favor with DS and they are not willing to let go their current practice, while the pharmacists are eager to have DS. Less is known about the expectations and perceptions of the GPs, pharmacists and the public towards the DS. This study explores the GPs', pharmacists', and public view on dispensing separation. Data were collected through face-to-face interviews, social media (Facebook and whatsapp) then audio recorded, and later were transcribed verbatim. The sample size was only five GPs, three pharmacists and four public due to limitations that cannot be counter measured. Three main themes that emerged are: inconvenience versus patients' safety, business at stake, and comfort zones. In terms of inconvenience versus patient safety,